Fitotoxidez do nitrato de cobre em culturas agrícolas cultivadas em latossolos - Engelhardt, Mateus Moreira (2018)
Copper is a micronutrient for organisms, but in high concentrations may cause negative effects on various forms of life. The assessment of toxicity caused by chemical compound in the environment shall be based on biological parameters sensitive to the contaminant. The values of EC50, EC20, and EC10 are indicated to show the sensitivity of the species with the increase of contaminant concentration. The objective of this study is to evaluate the behavior of different species through different concentrations of Cu nitrate in the soil. The species Triticum aestivum (wheat), Zea mays (maize), Oryza sativa (rice), Phaseolus vulgaris (common beans), Glycine max (soybeans), and Raphanus sativus (radish) cultivated in the soils typic dystrophic Red-Yellow Latosol (LVAd) and typic dystroferric Red Latosol (LVdf) were used. The species were cultivated in pots in a greenhouse. Copper concentrations were 0, 75, 150, 300, 600, 800, 1000, 1200 mg/kg dry soil. The experiment was in a randomized complete design with four replications. Measurements of biological variables, such as shoot dry matter, plant height, stem diameter, and number of leaves were carried out, in addition to determining Cu content in the leaves. The LVAd showed higher sensitivity than the LVdf when considering EC50 values. The species T. aestivum, Z. mays, and O. sativa were more sensitive than P. vulgaris, G. max and R. sativus.